2016
DOI: 10.1080/20477724.2016.1238186
|View full text |Cite
|
Sign up to set email alerts
|

Identification, production and assessment of twoToxoplasma gondiirecombinant proteins for use in aToxoplasmaIgG avidity assay

Abstract: The IgG avidity assay is an important tool in the management of suspected toxoplasmosis in pregnant women. This study aimed to produce new Toxoplasma gondii recombinant proteins and to assess their usefulness in an IgG avidity assay. Toxoplasma positive and negative serum samples were used, the former were categorized into low (LGA) and high (HGA) IgG avidity samples. Immunoblots were performed on 30 T. gondii cDNA clones to determine the reactivity and IgG avidity to the expressed proteins. Two of the clones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…However, due to the various limitations of avidity tests based on these antigenic preparation, new diagnostic tools that might improve the performance of avidity tests to distinguish between recent and past phases of toxoplasmosis are tested. In the past 20 years, several studies have reported the use of single recombinant antigens [ 44 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], mixture of proteins [ 44 , 67 , 68 ] or chimeric proteins [ 69 ] in the determination of IgG avidity ( Table 1 ). All these antigens have been obtained in Escherichia coli expression systems and purified by affinity chromatography.…”
Section: Recombinant Antigens In Igg Avidity Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the various limitations of avidity tests based on these antigenic preparation, new diagnostic tools that might improve the performance of avidity tests to distinguish between recent and past phases of toxoplasmosis are tested. In the past 20 years, several studies have reported the use of single recombinant antigens [ 44 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], mixture of proteins [ 44 , 67 , 68 ] or chimeric proteins [ 69 ] in the determination of IgG avidity ( Table 1 ). All these antigens have been obtained in Escherichia coli expression systems and purified by affinity chromatography.…”
Section: Recombinant Antigens In Igg Avidity Testsmentioning
confidence: 99%
“…Furthermore, Elyasi et al [ 64 ] suggested better performance of avidity ELISA based on GRA6 recombinant antigen than a commercial Euroimmun avidity ELISA for exclusion of a recent infection occurring less than 4 months previously. In 2016, Teh et al [ 66 ] found two novel proteins with diagnostic potential: AG12b encoded T. gondii apical complex lysine methyltransferase (AKMT) protein and AG18 encoded T. gondii forkhead-associated (FHA) domain-containing protein. These are completely new proteins not belonging to antigen families, such as SAG, GRA, MIC, and ROP groups which were tested in the diagnosis of toxoplasmosis.…”
Section: Recombinant Antigens In Igg Avidity Testsmentioning
confidence: 99%